1998
DOI: 10.1007/s003300050336
|View full text |Cite
|
Sign up to set email alerts
|

Intraurethral ultrasound: diagnostic evaluation of the striated urethral sphincter in incontinent females

Abstract: The aim of our study was to evaluate the striated urethral sphincter (rhabdosphincter) in incontinent females by means of intraurethral ultrasound (IUUS). Thirty-four incontinent and 11 continent female patients were examined by means of 12.5-MHz endoluminal ultrasound (US). The distance between the inner contour of the sphincter muscle and the US catheter was measured in the contracted and the non-contracted condition. The US findings were correlated with those obtained by urodynamic studies. Partial or compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 14 publications
2
34
0
3
Order By: Relevance
“…19,32,43,52,80,[97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116] The lead authors of these studies were contacted by letter and asked to provide further information. Four authors responded with all of the requested data.…”
Section: Results Of Contacting Authorsmentioning
confidence: 99%
“…19,32,43,52,80,[97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116] The lead authors of these studies were contacted by letter and asked to provide further information. Four authors responded with all of the requested data.…”
Section: Results Of Contacting Authorsmentioning
confidence: 99%
“…After repeating the measurement at least 5 times in every patient, they concluded that ⌬RTD was a reproducible measurement because differences in the same patient were negligible. 13 Frauscher et al 7 and Strasser et al 13 found a negative correlation between rhabdosphincter contractility, as measured by ⌬RTD, and grade of stress urinary incontinence.…”
Section: Table 1 Mean Differences In Urethral Sphincter Morphologic Mmentioning
confidence: 97%
“…[4][5][6][7] Two studies have shown that urethral sphincter area and circumference decrease as the grade of stress incontinence increases. 4,5 One study found that the sphincter is thinner in incontinent women than in asymptomatic women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urol Nephrol Open Access J 4 (6) [22] also known as the urogenital sphincter acts as a secondary sphincter to control the urine flow through the urethra. Loss of sphincter function in women with SUI [24] partially or completely has also been detected using a intraurethral ultrasound (IUUS).…”
Section: Introductionmentioning
confidence: 99%